Emerging Trends and Innovations in Fuel Cell Research: Materials and Beyond - Sua, Lutfu S.; Balo, Figen (wiley, 2025)
Hydrogen is on its way to become a significant source of energy in the future. Fuel cell is one of the devices that run on hydrogen. In this electrochemical system, water vapor is the waste product and clean electricity can be produced. There are various types of fuel cells. The production of fuel cells is still an expensive process, despite the great expectations surrounding hydrogen vehicles, especially with regard to the potential to increase the autonomy of electric mobility. The search for new materials will bring further cost savings. The characteristics of new materials must not only focus on cost reduction, but also on improving certain properties, such as improving electrochemical performance under low humidity reagent gas conditions, maintaining mechanical stability of membranes even at temperatures above a certain point, preventing corrosion of components, and reducing overall size. This study involves a detailed analysis of the recent improvements, materials, and innovations in fuel cells. A strategic evaluation will then be carried out using multi-criteria decision analysis to select the most effective fuel cell among the popular fuel cells. © 2025 Scrivener Publishing LLC. All rights reserved.
Keywords: Fuel cell; H2 generation; Hydrogen; Renewable energy; Sustainability